End-to-end synchronization in packet switched networks - Almeida, Nuno (1991)
The provision of real time services through a Packet Switched Network, requires the adoption of end-to-end synchronization methods. Several of these methods, are compared and a specific hardware solution is discussed. Results obtained through a specially designed Simulation Programme are included, for several network time delay jitter distributions and synchronization methods. These results are used to evaluate systems and design parameters.